ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT ADIRA DINAMIKA MULTI FINANCE TBK PERIODE 2020-2024 - Ida Subaida; Yulia Variska Putri; Rika Maulidah (Fakultas Ekonomi dan Bisnis, 2026)
This study aims to analyze the financial performance of PT Adira Dinamika Multi Finance Tbk during the period 2020–2024 using financial ratio analysis. The ratios examined include liquidity ratios (Current Ratio and Cash Ratio), solvency ratios (Debt to Asset Ratio and Debt to Equity Ratio), profitability ratios (Return on Assets and Return on Equity), and activity ratios (Fixed Asset Turnover and Total Asset Turnover). This research employs a quantitative descriptive approach using secondary data obtained from the company’s annual financial reports published by the Indonesia Stock Exchange (IDX). The results indicate that the company’s liquidity condition is generally good, as both the Current Ratio and Cash Ratio remain above industry standards, although cash management still shows fluctuations. From the solvency perspective, the company exhibits relatively high leverage, reflected by Debt to Asset Ratio and Debt to Equity Ratio values that exceed industry benchmarks, indicating a considerable dependence on debt financing. Profitability ratios show that Return on Assets and Return on Equity are still below industry standards, suggesting that asset utilization and returns to shareholders have not been optimal. In terms of activity ratios, Fixed Asset Turnover demonstrates very efficient use of fixed assets, while Total Asset Turnover remains low, indicating that overall asset utilization in generating sales needs improvement. Therefore, the company is expected to optimize asset management, improve capital structure, and enhance profitability to achieve more sustainable financial performance.